THE EMPOWERMENT OF KARANGPANDAN COMMUNITY THROUGH ECOLOGY-BASED LIVING BARN PLANT ARRANGEMENT SKILLS TRAINING FOR STRENGTHENING THE TOURISM - Sunarmi (International Journal of Social Science, 2021)
Sawahan Karangpandan Village is one of the villages in Karangpandan, Karanganyar Regency, and it is a strategic village being a tourism village.Society has not entirely aware of the potential. Mostly, they earned their living by culinary business, planting living barn plants, decorative plants, and farming. It is strategic to be developed as a business during the Covid-19 pandemic. The PPM, the ISI Surakarta team, considers the importance of providing skilful education for the Sawahan Karangpandan community through the thematic Community Service Program in ISI Yogyakarta. The method employed is using Rapid Rural Appraisal (RRA) methodand Participatory Rural Appraisal (PRA) method. The result of Community Service shows that Rapid Rural Appraisal (RRA) method and Participatory Rural Appraisal (PRA) method can provide valuable skills to the community.Because the people in Sawahan village support training activities such as IT-based MSME's promotion strategy, decorative plants and living barn plants-based competition, and education for the strategy to exist during the pandemic. The research result of training skills in arranging and promotion can be seen on Instagram with the following address https://instagram.com/kkn21_karangpandan?utm_medium=copy_link Keywords: Empowerment, Promotion, IT, Arrangement, Education.